In Vitro Goat Fermentation of PUFA-Diet Supplemented with Yeast and Curcuma xanthorrhiza Roxb - E Sulistyowati; A Sudarman; K G Wiryawan; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2014)
This in vitro experiment was conducted to evaluate the ruminal performances of polyunsaturated fatty acid (PUFA)-diet (containing PUFA with 80% concentrate and 20% King grass) supplemented with yeast and C. xanthorrhiza Roxb. Experimental design was completely randomized block design of 4 x 4 with ruminal liquor derived from 4 slaughtered goats and 4 treatments (PD0-no supplement, PDY- 0.5% yeast, PDC-2% curcuma, and PDM- 0.5% yeast + 2% curcuma). Variables measured were pH, N-NH3, total and partial VFA (volatile fatty acid), protozoa population, and CH4 (methane). Results showed that the lowest (P<0.05) organic (59.63%) and dry matter (58.00%) digestibilities were found in PDM. In in vitro, this diet was also showing quantitatively low in N-NH3 (8.73 mM) and protozoa population (7.90±4.09 103 cfu/mL). On the other hand, it showed numerically high in VFA production (45.27 mM) and pH (6.74), yet low in CH4 (13.43% v/v). Based on these data, PDM was considered the most potential diet to improve nutrient metabolism in rumen of goat, in vitro.Key words: PUFA- diet, yeast, curcuma, in vitro fermentation